Reconsidering Journalist Safety Training - Høiby, Marte (2020)
Safety training courses and manuals are designed to provide journalists with guidance to assess and mitigate risk. In this article, we ask whether content of such training and guidance is informed by actual threats and risks relevant to journalists working in the field. Departing from our own previous research about threats and dangers faced by journalists working in conflict zones or covering dangerous beats, and a review of the literature addressing the issue of safety manuals for journalists, we evaluate the content of five safety-training documents. Of these, two are descriptions of internationally-focused safety courses, two are safety manuals produced for a national audience, and one is a handbook focusing specifically on safety for women reporters in the Arab region. The purpose is to identify various aspects of safety addressed in training and manuals offered to locally and internationally-deployed journalists—and illuminate how they may differ in focus and approach. Through a comparison of the content of the selected manuals and course descriptions, we conclude that these trainings and manuals to some extent address specific variations in context, but that detailed attention towards gender differences in risk and other personal characteristics are not given equivalent weight. The international training focuses excessively on physical environment issues (such as those of a ‘hostile environment’), while the manuals with national or regional focus are practice-oriented and largely take a journalistic point of departure. We argue that training and manuals can benefit from considering both these aspects for risk assessment, but recommend that addressing journalistic practice and personal resources is fundamental to all journalist safety training since it is at the personal, practical, and media organisational levels that the mitigation encouraged by these trainings can happen.